Identifying Key Competitive Factors in Industrial Enterprises Producing and Supplying Chemical Products in the Northwest Region of the Country Using Thematic Analysis - Sonboli , Amin; Bafande Zendeh, Alireza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This article aims to identify the key competitive factors in industrial enterprises involved in the production and supply of chemical products in the northwest region of the country using the thematic analysis method. Methodology: The research method is qualitative and exploratory. Data were collected using thematic analysis and through purposeful and in-depth interviews with 20 experts and specialists in the fields of market management and competition. Initial coding and the definition of sub-themes and main themes facilitated the identification of factors affecting the competitiveness of active industrial enterprises. Findings: Data extracted from in-depth interviews were analyzed using thematic analysis in three stages: open coding, axial coding, and selective coding. In the initial coding stage, 82 keywords were identified. During the second stage, 56 concepts were extracted, and in the third stage, the analysis resulted in the extraction of 30 basic codes, 10 sub-themes, and 4 main themes. Conclusion: The results of the study indicate that the key competitive factors in industrial enterprises engaged in the production and supply of chemical products in the northwest region include: environmental factors (micro and national levels), internal organizational factors (market-oriented perspective, knowledge-oriented perspective, and resource-based perspective), factors creating perceived value (perceived value of competitors and the market towards the enterprise, perceived value of customers towards the enterprise), and competitiveness components (internal performance of the enterprise, enterprise performance regarding customers, enterprise performance in the market).